Il figlicidio: un delitto inspiegabile? - Di Gianfrancesco, Elvira (Il sogno della farfalla, 2005)
This article discusses the crimes of infanticide and filicide exploring them from a statistical, historical, socio-cultural and psychopathological point of view. The author points out the difficulty of crime prevention and the complexities of the diagnosis of these homicides, focusing attention on the present limitations of psychiatric competence. The lack of research into the unconscious, which has characterized psychiatry, constitutes the unsurmountable limit in the study of these “clinical cases”. In Massimo Fagioli’s theory, the “lack of affectivity” constitutes the main psychopathological disorder responsible for many apparently inexplicable murders. The discovery of the “annulment drive” is once again of key importance in understanding the non-conscious reality of human beings. The article then goes on to explore the legal concept of “incapable of understanding and intending” which is currently in use in Italian forensic psychopathology. An examination of the criminological aspects of recent news reports on these crimes follows.